Characterization of genes required for pilus expression in Pseudomonas syringae pathovar phaseolicola. - Roine, E (1996)
Nonpiliated, phage phi 6-resistant mutants of Pseudomonas syringae pv. phaseolicola were generated by Tn5 transposon mutagenesis. A P. syringae pv. phaseolicola LR700 cosmid library was screened with Tn5-containing EcoRI fragments cloned from nonpiliated mutants. The cosmid clone pVK253 complemented the nonpiliated mutant strain HB2.5. A 3.8-kb sequenced region spanning the Tn5 insertion site contained four open reading frames. The transposon-inactivated gene, designated pilP, is 525 bp long, potentially encoding a 19.1-kDa protein precursor that contains a typical membrane lipoprotein leader sequence. Generation of single mutations in each of the three remaining complete open reading frames by marker exchange also resulted in a nonpiliated phenotype. Expression of this gene region by the T7 expression system in Escherichia coli resulted in four polypeptides of approximately 39, 26, 23, and 18 kDa, in agreement with the sizes of the open reading frames. The three genes upstream of pilP were designated pilM (39 kDa), pilN (23 kDa), and pilO (26 kDa). The processing of the PilP precursor into its mature form was shown to be inhibited by globomycin, a specific inhibitor of signal peptidase II. The gene region identified shows a high degree of homology to a gene region reported to be required for Pseudomonas aeruginosa type IV pilus production.